Range extension and first report of the fish Lagocephalus inermis (Tetraodontiformes: Tetraodontidae) from Digha, Northeast Coast of India (UNED Research Journal, 2016)
The occurrence of Lagocephalus inermis (Temminck & Schlegel, 1850) is reported for the first time from Digha extending the range of the species to the east coast of India based on one specimen. This species was already reported from south-eastern coast of India and western coast of India. The 196 mm standard length specimen from Digha Mohana is described in detail.
Keywords: Lagocephalus inermis; Tetraodontidae; North-east coast of India; Digha; Bay of Bengal